An assessment of the role of money in Nigerian general election - Chul, Abubakar Auwal; Ismail, Mohd Mahadee; Ku Samsu, Ku Hasnita (International Organization Of Scientific Research, 2017)
This article is an attempt to assess the role of money in Nigerian election and political processes as a hindrance to strengthening democracy.Money is needed for democracy because much of its political activity simply could not occur without it. However, when discussing its costs and benefits one should know that the misuse of money in politics can create some major problems for a political regime. Vote buying denies a society the democratic principle of transparency and accountability because vote buyers are under no obligation to serve the masses interest. It discovered and argued that money Nigeria politics ’being an acceptable means of electoral financing, shifted to mild vote buying in the year 1960s during the second republic and later become pervasive and more widespread; especially since 1999. The article concludes with recommendation of reforms, political education to the civil society and enforcement of election laws.